Ayurvedic therapy (Shirodhara) for Insomnia: A Case Series. Issue 1 (January 2014) - Vinjamury, Sivarama Prasad; Vinjamury, Manjusha; Der Martirosian, Claudia; Miller, Judith
Background: Insomnia is one of the most common complaints faced by primary care practitioners after pain. Non-pharmacological management of Insomnia that is noninvasive is gaining interest among patients with insomnia. Purpose: To determine the feasibility of recruiting and retaining participants in a clinical trial on shirodhara, Ayurvedic oil dripping therapy, for insomnia in the United States and also to investigate the therapeutic usefulness of Shirodhara for insomnia using standardized outcome measures. Design: Case series. Study Intervention and Data Collection: Shirodhara with Brahmi oil was done for 45 minutes on each participant for 5 consecutive days. Insomnia Severity Index (ISI) was used to evaluate the severity of insomnia as well as to determine the response to Shirodhara therapy. Data were collected at baseline, end of the treatment (day 5) and 1 week after the treatment ended (follow-up). Results: Two males and eight females with a mean age of 40 years (range 23 to 72), SD ± 14.2, were enrolled in the study. One dropped out of the study, but all remaining nine participants experienced improvement at the end of treatment. The percentage of improvement range varied from 3.85% to 69.57%. At follow-up, most participants continued to improve. Comparison of means between baseline and day 5 indicated an overall significant improvement (P < .005), but in a comparison of baseline vs 1 week posttreatment the improvement was not significant (P < .089). No adverse events were reported during the study. Conclusion: Shirodhara with Brahmi oil may be beneficial for moderate to severe insomnia. It is feasible to recruit and retain participants for such therapies in the United States. It is important to validate these findings and investigate the mechanism of action using a larger sample and rigorous research design.